2005
DOI: 10.1002/pssa.200520077
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐reflectometry monitoring of the GaN growth by MOVPE using SiN treatment: study and simulation

Abstract: The SiN treatment of the sapphire substrate for GaN growth induces a spectacular effect on the in situ reflectometry monitoring signal. Different growth modes are observed. The evolution of the reflectometry signal is simulated by the scattering theory approximation. The point-by-point analysis reveals that the roughness (rms) increases in the first region where the growth mode is dominated by the formation of isolated and three-dimensional hillocks. The rms attains a maximum value exceeding that authorized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The nucleation was done using the socalled ''Si/N-treatment'' procedure. The optimum growth conditions and the details of the Si/N-treatment growth process were reported elsewhere [6][7][8][9][10][11]. TMG, ammonia, silane and Cp 2 Mg were used as Ga, N, Si and Mg precursors with a mixture of H 2 and N 2 as the carrier gas.…”
Section: Methodsmentioning
confidence: 99%
“…The nucleation was done using the socalled ''Si/N-treatment'' procedure. The optimum growth conditions and the details of the Si/N-treatment growth process were reported elsewhere [6][7][8][9][10][11]. TMG, ammonia, silane and Cp 2 Mg were used as Ga, N, Si and Mg precursors with a mixture of H 2 and N 2 as the carrier gas.…”
Section: Methodsmentioning
confidence: 99%
“…Fitouri et al found a similar behavior, once the coalescence process takes place. 27 The n f profile versus thickness is given in Fig. 8.…”
Section: Determination Of Refractive Index Evolutionmentioning
confidence: 99%
“…Moreover, because of spontaneous phenomena such as diffusion and segregation, other complex heterostructures have unstable physical properties during growth, leading to changes in solid composition, surface morphology, and growth rate (V g ). 17,18 Therefore, a large spectral range of the incident beam is needed to investigate some of these phenomena.…”
Section: Manufacturingmentioning
confidence: 99%